2009
DOI: 10.5194/nhess-9-913-2009
|View full text |Cite
|
Sign up to set email alerts
|

The Swiss flood and landslide damage database 1972–2007

Abstract: Abstract. In Switzerland, floods, debris flows, landslides and rockfalls cause damage every year affecting property values, infrastructure, forestry and agriculture. As population and settled areas have increased, the damage potential has also become greater. Information about natural hazard events that caused any damage is needed for hazard mapping and further decision making. This is why the Swiss Federal Research Institute WSL has been systematically collecting information on flood and mass movement damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
203
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(225 citation statements)
references
References 23 publications
5
203
0
5
Order By: Relevance
“…Newspaper data allow either investigation or complete information of past landslides (Cuesta et al, 1999;Devoli et al, 2007;Kuriakose et al, 2009), floods (Rappaport, 2000;Agasse, 2003;Maples and Tiefenbacher, 2009;Adhikari et al, 2010), or both types of phenomena (Hilker et al, 2009). Collected data allow either analysis of the evolution of societal hazard perception (Llasat et al, 2009) or the estimation of direct financial damage as well as fatalities and injured people (FitzGerald et al, 2010).…”
Section: Methodological Approachmentioning
confidence: 99%
“…Newspaper data allow either investigation or complete information of past landslides (Cuesta et al, 1999;Devoli et al, 2007;Kuriakose et al, 2009), floods (Rappaport, 2000;Agasse, 2003;Maples and Tiefenbacher, 2009;Adhikari et al, 2010), or both types of phenomena (Hilker et al, 2009). Collected data allow either analysis of the evolution of societal hazard perception (Llasat et al, 2009) or the estimation of direct financial damage as well as fatalities and injured people (FitzGerald et al, 2010).…”
Section: Methodological Approachmentioning
confidence: 99%
“…Holub and Hübl, 2008). During the large storm events of 2005 in Switzerland (Bezzola and Hegg, 2007), an estimated one third to one half of the total damage, at a cost of three billion Swiss francs, was associated with sediment transport processes (Nitsche et al, 2011), based on data from the Swiss flood and landslide damage database (Hilker et al, 2009). In most of the widely used bedload equations, the incipient motion of individual sediment particles (and thus the occurrence of bedload transport in a stream) is described by a critical discharge or shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…This yields an average fatality rate of 0.3. In Switzerland, Hilker et al (2009) (Guzzetti et al 2006). A national Italian investigation on landslide risk in the twentieth century revealed that at least 7799 casualties were reported, 5831 lives were lost, 108 missing, and 1860 injured (Guzzetti et al 2003).…”
Section: Landslide Characteristics and Methods For Quantification Expmentioning
confidence: 99%
“…Previous scientifically published quantification on fatalities are, as far as we know, calculated frequency rates for average number of fatalities per event, year, month, day, intensity, area of occurrence or expressed as the number of deaths per 100,000 inhabitants for a given population over a predefined time period (Cascini et al 2008;Giannecchini and D'Amato Avanzi 2012;Guzzetti et al 2005b;Hilker et al 2009;Pereira et al 2014;Salvati et al 2010). Methodologically, the studies differ concerning which observation inclusion criteria that are used when deriving a fatality (or mortality) rate.…”
Section: Factors Affecting Susceptibility (S F )mentioning
confidence: 99%